Danger of co-administration ferric carboxymaltose and denosumab: hypophosphatemia - Aysun Seker; Nurdan Senturk Durmus (The Egyptian Journal of Internal Medicine)
Abstract Both denosumab-induced hypocalcemia and ferric carboxymaltose infusion-related hypophosphatemia have been extensively documented. There are significant risks associated with combining ferric carboxymaltose parenteral infusions and denosumab, including potentially life-threatening electrolyte imbalances such as hypocalcemia and hypophosphatemia. Developing monitoring strategies for electrolyte abnormalities can be facilitated by the increased awareness of this interaction. We present the case of a 62-year-old female patient who developed severe, symptomatic hypocalcemia and hypophosphatemia despite having normal renal function. These abnormalities occurred concomitantly during treatment with denosumab for osteoporosis and ferric carboxymaltose for iron deficiency anemia.